Diagnosis Bentuk Kesulitan Belajar Matematika pada Siswa Kelas VI di SDN 40 Ampenan - Wani, Ityam; Witono, A. Hari; Radiusman (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This study aims to analyze the forms of mathematics learning difficulties and the factors that influence them in sixth-grade students of SDN 40 Ampenan. The study used a descriptive method with data collection techniques in the form of observations and questionnaires given to 16 students as respondents. The questionnaire instrument consisted of 20 statements used to identify indicators of mathematics learning difficulties. The results showed that there were two students who experienced significant difficulties in understanding numbers, estimating quantities, and solving story problems. Factors causing these learning difficulties included internal factors, such as low interest and weak problem-solving skills, as well as external factors such as lack of environmental support and family socio-economic conditions. Learning observations also showed the need for additional assistance for students who experienced difficulties. This study emphasized the importance of adaptive learning interventions and environmental support to help students overcome mathematics learning difficulties optimally.